"Tell the truth": Political trust and expectations of politicians in Iceland 2020-2023 - Valgarðsson, Viktor Orri; Sigurgeirsdóttir, Sigurbjörg (Stofnun stjórnmála og stjórnsýslu, 2023)
Political trust in Iceland collapsed in 2008 and did not appear to recover in the following years despite substantial economic growth. In 2021-2022, trust seemed to have reached pre-crisis levels, but it is unclear whether this was a temporary increase due to the COVID-19 pandemic or indicative of a more permanent development. In this study we explore the trajectory of political trust in Iceland in recent years, with a focus on two distinct sources of trust: competence and integrity. Our hypothesis is that the 2008 economic crisis did not only damage the Icelandic people‘s view of politicians‘ competence, but also their integrity. We test this hypothesis indirectly by analysing the relationship between political trust and expectations of politicians in Iceland, using data from surveys conducted yearly between 2020 and 2023. Our results suggest that Icelanders who prioritize the integrity of politicians tend to trust MPs less than those who prioritize attributes related to competence, taking partisanship and demographic factors into account. The results also suggest that the public placed more priority on competence attributes in 2020-2022 but in 2023 the emphasis appears to have shifted towards integrity and in that year, political trust declined to a similar level as before the pandemic. These findings suggest that when the Icelandic public places more priority on integrity, their levels of political trust are low, but when competence is valued more, trust is higher. This may explain why political trust does not appear to have recovered after the financial crisis despite economic recovery if Icelandic politicians have not regained their reputation for integrity. Pólitískt traust hrundi á Íslandi árið 2008 og náði sér ekki á strik næstu ár þrátt fyrir verulegan efnahagsbata. Árin 2021-2022 virtist traustið hafa náð fyrri hæðum, en óljóst er hvort það var tímabundin aukning vegna heimsfaraldurs eða merki um varanlega þróun. Í þessari rannsókn skoðum við þróun pólitísks trausts á Íslandi undanfarin ár, með ...